2014
DOI: 10.4314/njp.v41i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Empiric antibiotic prescription among febrile under-five Children in the University of Port Harcourt Teaching Hospital, Rivers State, Nigeria

Abstract: Background: More than 97% of febrile infants and young children have self-limiting viral infection and therefore, would not require antibiotics. Over prescription of antibiotics increases antibiotics exposure and development of resistance among patients. There is need to evaluate empiric antibiotic prescription in order to limit its use to only febrile children with bacterial infection. Aim and Objectives: The aim of this study was to determine the prevalence of empiric antibiotic prescription among febrile un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In fact, 96.4% of the children who received antibiotics during their febrile illnesses in this study also had a cough. This finding correlates with reports from Nigeria [ 14 ], Uganda [ 25 ] and Vietnam [ 26 ] where upper respiratory tract infections (common cold) were a cause of up to 83.7, 70.5 and 63% antibiotics exposure among children respectively, and corroborates that reported among adult patients in the Kingdom of Saudi Arabia [ 35 ]. Similarly, in surveys conducted in rural China [ 31 ] and Indonesia [ 37 ], antibiotics were 42% more likely to be used if the child had a cough and/or common cold.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, 96.4% of the children who received antibiotics during their febrile illnesses in this study also had a cough. This finding correlates with reports from Nigeria [ 14 ], Uganda [ 25 ] and Vietnam [ 26 ] where upper respiratory tract infections (common cold) were a cause of up to 83.7, 70.5 and 63% antibiotics exposure among children respectively, and corroborates that reported among adult patients in the Kingdom of Saudi Arabia [ 35 ]. Similarly, in surveys conducted in rural China [ 31 ] and Indonesia [ 37 ], antibiotics were 42% more likely to be used if the child had a cough and/or common cold.…”
Section: Discussionsupporting
confidence: 91%
“…The study population comprised children aged 6-59 months with fever presenting to the tertiary health facility during the study period. A sample size of 210 participants was estimated using the single population proportion formula based on a proportion of antibiotic exposure (P) of 83.7% [ 14 ], with a marginal error (D) of 5%, a standard normal value (Z) corresponding to 95% certainty (1.96).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the present study, nearly all the antibiotics prescribed (98.9%) were based on signs and symptoms indicative of bacterial infections, and > 98% were broad-spectrum agents for all possible pathogens associated with the site of infection. This largely indicates that most of the antibiotics prescribed for the under-five children were empirically prescribed, thereby further corroborating the widespread empirical nature of antibiotic prescribing in many developed and developing countries36,4649.…”
Section: Discussionsupporting
confidence: 53%
“…The situation report presented by Nigeria Centre for Disease Control revealed a trend of the wide spread of resistance strain to watch a group of antibiotics according to World Health Organization categorization [7]. In a study in Port Harcourt, Rivers State, Nigeria, it was observed that the Upper respiratory tract infection (83.7 %) and diarrhoea (55.9%) were significantly associated with empirical antibiotic prescription (P=0.05 and 0.002 [8]. Empirical prescription contributes greatly to antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%